2016
DOI: 10.3146/ps14-17.1
|View full text |Cite
|
Sign up to set email alerts
|

Peanut Oil Stability and Physical Properties Across a Range of Industrially Relevant Oleic Acid/Linoleic Acid Ratios

Abstract: High oleic cultivars are becoming increasing prevalent in the peanut industry due to their increased shelf life compared to conventional cultivars. High oleic peanuts are typically defined as having oleic acid/linoleic acid (O/L) ratios ≥ 9, whereas most traditional varieties have O/L ratios near 1.5-2.0. In practice, this ratio can vary substantially among commercial material; accordingly, the goal of this study was to better understand the shelf life and physical properties of 16 model oil blends with O/L ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 22 publications
0
23
0
1
Order By: Relevance
“…Peanut seeds contain carbohydrates (105% to 20%), protein (16% to 36%), and oil (36% to 54%) as major constituents (Davis et al., ). They also contain many important functional components including coenzyme Q 10 (Pravst, Žmitek, & Žmitek, ), arginine, and polysterols, which make it a functional food (Akhtar, Khalid, Ahmed, Shahzad, & Suleria, ; Francisco & Resurrecion, ).…”
Section: Peanut: a Legume To Tackle Food Security Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Peanut seeds contain carbohydrates (105% to 20%), protein (16% to 36%), and oil (36% to 54%) as major constituents (Davis et al., ). They also contain many important functional components including coenzyme Q 10 (Pravst, Žmitek, & Žmitek, ), arginine, and polysterols, which make it a functional food (Akhtar, Khalid, Ahmed, Shahzad, & Suleria, ; Francisco & Resurrecion, ).…”
Section: Peanut: a Legume To Tackle Food Security Issuesmentioning
confidence: 99%
“…An important aspect of the peanut oil is the relative ratios of different fatty acids, which dramatically change with maturity (Pattee, Johns, Singleton, & Sanders, ; Sanders, ). Typically, a majority of peanut genotypes contain 36% to 67% oleic and 15% to 46% linoleic acid resulting in O/L ratios ranging from 1.19 to 4.46 (Davis et al., ; Norden, Gorbet, Knauft, & Young, ). Rapid changes taking place in climate can also influence the oil contents and its composition.…”
Section: Peanut: a Legume To Tackle Food Security Issuesmentioning
confidence: 99%
“…Thus, the oleic/linoleic ratio (O/L) for Kainong 17-15 was 19.82:1. In addition to nutritional properties, Davis et al (2016) and Janick (2014) evaluate peanuts and peanut products by the stability index (SI), which is O/L ratio. In addition, other researchers reported that the high stability index implies a good compositional quality of the product and can ensure better shelf life (Dhamsaniya et al 2012).…”
Section: Fatty Acid Compositions Of Peanut Cultivarsmentioning
confidence: 99%
“…Other oils and fats characteristics are also fire points, flash points [23], refractive index. Indeed, it was established a correlation between peanuts refractive index, peanuts oleic acid rate and peanuts linoleic acid rate such as increasing concentrations of oleic acid and corresponding of decreases in linoleic acid were associated with decreasing oil density, decreasing refractive index, and increasing viscosity [29]. The following table 4 showed the Malagasy peanuts compositions.…”
Section: Peanut Oil Characteristics and Compositionsmentioning
confidence: 97%